Click chemistry-based aptasensor for highly sensitive electrochemical detection of thrombin. Issue 25 (15th June 2017) - Liu, Qianrui; Hu, Qiong; Li, Lianzhi; Kong, Jinming; Zhang, Xueji
Abstract : In this study, a click chemistry-based electrochemical aptasensor is reported for the detection of thrombin. Abstract : In this study, a click chemistry-based electrochemical aptasensor is reported for the simple and fast detection of thrombin. Briefly, the thiol-terminated aptamer1 (Apt1) was first self-assembled on a gold electrode for the specific recognition of thrombin in the following step. After this, the azido-labeled aptamer2 (Apt2) was attached to the electrode via the formation of a sandwich structure with Apt1 and thrombin. The azido terminal was designed for the subsequent labeling of Apt2 with ethynylferrocene via electrochemically mediated Cu(i )-catalyzed azide–alkyne cycloaddition (eCuAAC), in which the active Cu(i ) was electrochemically generated in situ . Finally, the quantitatively labeled ethynylferrocene probes could be detected on the basis of differential pulse voltammetry (DPV) for the electrochemical detection of thrombin. Under optimal conditions, this aptasensor could detect thrombin down to 84 pM with a good linear response over the range from 0.1 nM to 1000 nM. In addition, it exhibited excellent specificity in the quantitative detection of thrombin and also showed good detection reliability in serum samples.